Whither U.S. inflation and interest rates? - David Andolfatto (Latin American Journal of Central Banking (LAJCB), 2025)
I consider a long-term outlook for the U.S. economy. My thesis is that the U.S. has moved from a deflationary regime to an inflationary regime. The shift is associated with China's emergence as a bona fide geopolitical rival to the U.S. and what this geopolitical event implies for the supply and demand for U.S. Treasury securities going forward. U.S. fiscal deficits are likely to remain large. The growth in the global demand for U.S. Treasury securities shows signs of slowing. Together, these forces are likely to exert upward pressure on U.S. inflation and interest rates.
Keywords: 330; Demand; Monetary and fiscal Policy; Supply; U.S. treasury securities